2016
DOI: 10.1002/jsfa.8007
|View full text |Cite
|
Sign up to set email alerts
|

Yeast derived from lignocellulosic biomass as a sustainable feed resource for use in aquaculture

Abstract: The global expansion in aquaculture production implies an emerging need of suitable and sustainable protein sources. Currently, the fish feed industry is dependent on high-quality protein sources of marine and plant origin. Yeast derived from processing of low-value and non-food lignocellulosic biomass is a potential sustainable source of protein in fish diets. Following enzymatic hydrolysis, the hexose and pentose sugars of lignocellulosic substrates and supplementary nutrients can be converted into protein-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
152
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 116 publications
2
152
0
3
Order By: Relevance
“…[76][77][78] This implies that macroalgal carbohydrates wileyonlinelibrary.com/jsfa can be used as alternative carbon sources in fermentation processes to replace conventional carbohydrate sources like simple sugars. The chemical composition of the macroalgal biomass is complementary to lignocellulosic biomass, 79 which may facilitate yeast production by cofermentation in a biorefinery approach. The macroalgae can supply essential nutrients like nitrogen and minerals that are lacking in lignocellulosic biomass.…”
Section: Processing For Compound Feed Applicationmentioning
confidence: 99%
“…[76][77][78] This implies that macroalgal carbohydrates wileyonlinelibrary.com/jsfa can be used as alternative carbon sources in fermentation processes to replace conventional carbohydrate sources like simple sugars. The chemical composition of the macroalgal biomass is complementary to lignocellulosic biomass, 79 which may facilitate yeast production by cofermentation in a biorefinery approach. The macroalgae can supply essential nutrients like nitrogen and minerals that are lacking in lignocellulosic biomass.…”
Section: Processing For Compound Feed Applicationmentioning
confidence: 99%
“…Yeast supplementation favors the digestibility of crude protein . However, some animals may have difficulties digesting intact yeast cells, but the removal of the cell wall enhances the yeast extract's digestibility …”
Section: Discussionmentioning
confidence: 99%
“…31 However, some animals may have difficulties digesting intact yeast cells, but the removal of the cell wall enhances the yeast extract's digestibility. 32 A study by Shen et al 10 reported that supplementation of yeast culture in diets to weanling piglets improved total tract digestibility of DM, CP, and GE. Nochta et al 33 also reported that supplementation of a mannan-containing feed additive led to higher ileal digestibility of nutrients, particularly indispensable amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial ingredients have proven to be high quality protein sources with the ability to mitigate the negative effects of plant-derived proteins [11]. Microbial ingredients such as yeast and bacteria contain bioactive compounds with immunemodulating properties that improve the changes caused by SBM [12-14].…”
Section: Introductionmentioning
confidence: 99%